FRI0126 Characterization of Patients' Adherence and Persistence Profile ("Drug Survival") in a "Real Life" Population of Patients Treated with Adalilumab. (9th June 2015) - Gendelman, O.; Shalev, V.; Dahlia Weitzman, D.; Chodick, G.; Amital, H.
Abstract : Background: Most studies use registry-based data that encompass primarily patients that are directly seen by rheumatologists. However, this type of information is usually biased since "real life" primary care setting not represented as in regular primary care setting hence less affect true adherence rates. Therefore the registry reported data is often incomplete and often more favorable than true reality. Objectives: To investigate the duration of treatment of Adalimumab (Humira), drug survival (by analysis of persistence and adherence variables) and the different variables that affect these outcomes. Methods: We conducted a retrospective cohort study using the database of the Maccabi Healthcare Services (MHS), which is the second largest HMO in Israel insuring 1.8-million enrollees. The study encompassed patients treated with adalilumab due to different indications. Each study group was analyzed using a sample of the entire cohort of patients that were treated with the drug. The proportion of drug covered (PDC) was defined as the quantity of adalimumab dispensed from the first dispense to the end of study or until the end of use adalimumab divided by the estimated expected use according to the relevant period of time. Results: All patients with at least one dispense of adalimumab between 1.1.2008 and 31.12.2013 were identified in the database. A random sample of patients by each indication was selected for the study according to MHS policy of not revealing the patient numbers. We included 1, 339 after deleting 133 patients due to data less than 90 days or due to less than one year from enrolment to MHS, their disease distribution according to indications was as following; Crohns' disease -316, rheumatoid arthritis -292, psoriatic arthritis-260, ankylosing spondylitis – 216, psoriasis-136, ulcerative colitis – 119. Fig. 1 depicts the distribution of PDC rates according to the following distribution (<20%, 20%>80%, >80%). It clearly illustrates that patients with psoriatic arthritis and ulcerative colitis are more adherent administering their medications compared to other disorders whereas females patients are less adherent. Logistic regression analysis revealed that factors associated with adherence rates below 80% were lower social economic status, having either ulcerative colitis or psoriatic arthritis, or being treated concomitantly with either sulfasalazine or prednisolone. Conclusions: By and large "real life" adherence studies show that most patients to do not adhere to proper adalimumab self-administration. Many efforts should be employed to improve the current persistence and adherence patterns. Disclosure of Interest: None declared